Design and Analysis of PTO Shaft for a Fighter Jet Aircraft Considering Gyroscopic Effects - U Pait, Ramakrishnaprasad; B Kandagalty, S; Rao, Rajath (International Journal of Engineering and Technology, 2018)
This paper shows an approach in designing a high-speed PTO (Power Take-Off) Shaft assembly system, which acts as a mechanical link between the engine and AMAD (Aircraft Mounted Accessory Drive), considering the gyroscopic effects when analyzing the static and dynamic behavior. Gyroscopic effect is one of the various parameters which effect the operation of the PTO system. Failure of this shaft will cut off all the hydraulics and other controls to the aircraft operation which can further lead to the loss of aircraft itself. FEA Tools, such as ANSYS is used for performing the desired analysis. An effort has been made to meet-up the critical speed margin, within which the PTO System operates. The system is also designed to counter the parallel and angular misalignments caused due to vibration or thermal expansion with the help of high-speed flexible coupling.Â